2020
DOI: 10.33549/physiolres.934397
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Documentation of Stimulus Velocity Tuning of Mechanically Induced Reflex Cough

Abstract: In order to clear airways and lungs defensive reflexes are provoked rather by the dynamic phase of mechanical stimulus. It is speculated that provocation of defensive response depends not only on stimulus duration but also on stimulus velocity. Fourteen adult rabbits were anaesthetized and tracheotomized. Mechanical stimulus was provoked by a mechanical probe introduced through the tracheotomy and rotated by a small electrical motor using a rotational velocity of 40 rpm/s and 20 rpm/s. Threshold, incidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(21 reference statements)
0
5
0
Order By: Relevance
“… 18 , 30 An animal study shows that the introduction of a rotating mechanical probe to mechanically stimulate the airway of anesthetized rabbits induces the cough reflex. 11 …”
Section: Evaluation Methods For Cough Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations
“… 18 , 30 An animal study shows that the introduction of a rotating mechanical probe to mechanically stimulate the airway of anesthetized rabbits induces the cough reflex. 11 …”
Section: Evaluation Methods For Cough Sensitivitymentioning
confidence: 99%
“…In an animal study, the incidence of cough reflex was related to the intensity, duration, and rate of mechanical stimulation. 11 But in human studies, these factors have not been explored. Also, like the study by Jones et al , 15 the effect difference caused by different vibration frequency and vibration position needs to be further studied.…”
Section: Evaluation Methods For Cough Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Cough can be elicited by the activation of mechanically sensitive vagal afferent nerves projecting to the large airways (some specialised Aδ fibres, commonly named cough receptors) and lungs [mechanoreceptors, including rapidly adapting receptors (RARs) and slowly adapting receptors (SARs)] (15). In preclinical animal studies, the invasive intratracheal mechanical stimulation was found to induce the cough reflex in anaesthetised rabbits/cats/dogs (16)(17)(18)(19)(20). For humans in clinical practice, the common area where the mechanical stimulation has been applied are the large airways level and the chest (8,9).…”
Section: Mechanical Challenge Testsmentioning
confidence: 99%